Semi‐quantitative risk assessment on the impact of port development to wellhead platform. (3rd December 2019) - Hermansyah, Heri; Kumaraningrum, Anggraini R.; Sommeng, Andy N.; Wijanarko, Anondho; Sahlan, Muhamad; Shariff, Azmi M.
Abstract: An offshore company intends to develop a new field by installing two wellhead platforms to accommodate the well production from this field. Based on port development plans, the locations of these platforms are closed to port dumping and commercial anchorage areas. This can affect the platform's safety. Therefore, risk assessment and mitigation studies are required to forecast the impact of the new wellhead platform project. In this research, a risk analysis was conducted using a semi‐quantitative risk analysis method to determine the value of total external risk that affects the safety of platforms and security of personnel. A sensitivity analysis was also conducted to identify the maximum likelihood factors that affect the risk values of platforms. The values for the new platforms were found to high‐risk levels. To ensure that the risks are more tolerable, risk mitigation tasks need to be executed. Such tasks should be conducted by the company and related governmental bodies, such that the risk value, can be reduced to medium risk level. The typical risk factor developed in this research can be used by related stakeholders to determine the risk value for the impact of port development on platforms during construction and operation.